From Principle to Practice: Youth engagement at the international summer course on the rights of the child - Pollack, Candice (Revue de l’Université de Moncton, 2015)
The United Nations Convention on the Rights of the Child creates an express obligation on State parties to take into consideration the views and opinions of children and youth in matters that affect them. State parties, children’s rights advocates, scholars, and non-profits have all recognized the importance of the right to participation, and have undertaken many different approaches to ensure the authenticity of the experience for children and young people. The following note details some of the accepted principles for meaningful youth engagement, and reflects back on the experience of the Youth Rapporteur Programme at the 2015 edition of the International Summer Course on the Rights of the Child.